Features Of Rickets In Children: Diagnosis, Causes, Treatment - Maksudova Khakimakhon Faizullaevna (Genius Journals, 2024)
The article outlines modern views on the frequency and causes of rickets in young children. Clinical, radiological and laboratory signs of the disease, classification of rickets, as well as its main forms - calcium deficiency, phosphate deficiency and vitamin D deficiency are presented. Diagnostic and differential diagnostic criteria are given. Particular attention is paid to issues of nonspecific and specific prevention, as well as treatment.
Keywords: young children; the role of vitamin D; phosphorus-calcium metabolism disorders,; rickets